The caretakers : a novel - Bestor-Siegal, Amanda (William Morrow, an imprint of HarperCollins Publishers, 2022)
Set in a wealthy Parisian suburb, an emotionally riveting debut told from the point of view of six women, and centered around a group of au pairs, one of whom is arrested after a sudden and suspicious tragedy strikes her host family--a dramatic exploration of identity, class, and caregiving from a profoundly talented new writer.